Pro - Kontra Kebijakan Tax Amnesty terhadap Kepatuhan Wajib Pajak di Indonesia - Noya Yukari Siregar (Universitas Bina Sarana Informatika, 2018)
Tax amnesty program in Indonesia is expected to increase the number of Taxpayers, then revenue from the tax increasing. However, the application of tax amnesty in Indonesia still raises the pros and cons. Tax amnesty program is not the first time applied in Indonesia, in previous years the implemented of tax amnesty program is considered failed because of lack of information disclosure so that taxpayers are reluctant to report assets owned. If the tax amnesty program is still applied in Indonesia, it is expected to not only remove taxpayer's right to tax but also increase taxpayer compliance in paying its obligation, so that it can increase tax revenue in the future. This research is done by literature study, and then analyzed by referring to the constitution, mass media, electronic media, etc. and also supported by library study related to tax amnesty.